Key Issues Note by the IMF Managing Director to the IMFC on the Global Economy and Financial Markets-Outlook and Policy Responses. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
NULL.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Emerging Market Risk; Financial Market Sentiment; Market; PP; Risk Appetite